Thermal characterisation of multi-walled carbon nanotube array fabricated with novel transfer technology - Toh, Devin Jian An (Nanyang Technological University, 2024)
This project evaluated the thermal characteristics of vertically aligned multi-walled carbon nanotube (VACNT) arrays through a comparative study between as-grown VACNT samples grown using Thermal Chemical Vapour Deposition (TCVD) system and transferred VACNT samples using CNRS-International-NTU-Thales Research Alliance’s (CINTRA) patented flip-chip bonding technique. The effect of the flip-chip bonding technique on VACNT adhesion to substrate was also investigated. Knowledge gained from this research contributes to the usage of VACNT in real-world applications. The comparative study between as-grown VACNT and transferred VACNT was performed using a Thermal Imaging Test and a Thermal Cycling Stress Test. The effect of varying VACNT heights was evaluated and compared during the tests. Results showed that taller as-grown VACNT had slower initial heating rates with lower equilibrium temperatures compared to shorter as-grown VACNT. Transferred VACNT also had poorer thermal characteristics compared to as-grown VACNT with slower heating rates and lower equilibrium temperatures. Transferred VACNT had much stronger VACNT-substrate adhesion compared to as-grown VACNT, with the latter experiencing corner delamination after 5 – 10 thermal cycles and total delamination between 13 – 27 thermal cycles. No structural changes were observed on the transferred VACNT even after 30 cycles.